Evaluation of electrical power losses of photovoltaic modules subjected to partial shading conditions in the three climatic regions of Cameroon - A. Dadjé; N. Djongyang; R. Tchinda (Revue des Énergies Renouvelables, 2017)
This paper studies the behavior of three types of photovoltaic panels operating under partial shading conditions in the three climatic regions of Cameroon. The phenomenon of partial shading constitutes one of the factors which drastically disrupt the electric power produced by the photovoltaic generators. It is to contribute to solve this problem that we modelled the PV panels operating in partial shading conditions under the climatic parameters of the study area. The analytical method combined with the iterative method are used for the determination of PV module parameters under partial shading conditions. Studies were carried out over a period of one year in three cities, respectively: Yagoua for the sudano-sahelian region, Tchollire in the sudanese region and Tibati in the southern equatorial region. Three types of PV panels were used {polycrystalline (MSX-60), monocrystalline (Shell SP70) and CIS thin film (Shell ST40)}. The electrical power losses of each type of panel were evaluated.